Work placements as narrative learning: stories for learning and for counterpoint. (25th July 2006) - Sims, David; Murray, Linda; Murakami, Kyoko; Chedzey, Katy
This paper reports on a study of work placement students in a British university, looking at the stories that they tell about what and how they learn on their placements. It argues that the stories told do not only relay the student's learning, but are also a part of how that learning takes place. Several of the stories seem to carry counter stories and the paper looks at several examples of students telling us both the story and its counter story, as if to express the need for both in their learning. This contrasts with the comparative univocality of some propositional learning. The paper suggests that narrative learning may be particularly appropriate when that which is being learned needs context, qualification and continuing development to make sense to the student.